O Programa de Saúde da Família no Ceará : uma análise de sua estrutura e funcionamento - Andrade, Francisca Maria Oliveira (1998)
The objective of this study was to contribute for the improvement of the Family Health Program ( FHP) developed in the State of Ceará, northeast Brazil, in terms of program functioning and impact. Based on the results, recomendations on interventions aimed to the main problems found were prepared. Self-administered questionnaires were answered by 82 (78%) secretaries of health of the municipalities where the program is being carried out, 230 (67,4%) physicians, 278 (81,5%) nurses and 2.507 (73,5%) community health agents working in the program. The FHP teams (composed mainly by physicians, nurses and health agents) also answered together, an specific questionnaire, with a response of 149 (43,6%). Many positive aspects of the program were found such as : many health activities being developed in some villages where, in the past, there was no regular assistance, including activities to reach groups like youth and elders; more frequently follow up of patients with chronic diseases like diabetes, and hypertension; almost all physicians and nurses working full time in the program; many health agents reporting that they were receiving technical support and refreshing courses from the other members of the team. Also a better organized referral system for patients in need of a more complex level of health care was found. According to secretaries, physicians and nurses there was a significant improvement of the quality of the assistance, that now is supposed to be more comprehensive. The problems found were: The majority of doctors and nurses had no labor rights guaranteed; an important number of health professionals were working in the program suitable qualification; a great diversity of salaries leading to a considerable turnover of doctors; lack of physicians willing to work in the poorest municipalities; an excessive number of families to follow by most of the teams; poor infrastructure of many local health facilities; teams providing assistance in many communities; insufficient provision of medicines; few activities of health control, just few intersetorial initiatives and lack of community participation. The conclusions of the study indicate that it is necessary a greater discussion among the federal, state and municipal health managers, including the effective participation of the local professionals, about the adjustments that need to be done in FHP. This discussion must happen before the important increase of number of health teams planned for the coming years. This study is expected to be also useful for other brazilian states that are developing, or planning to develop the program, as well as to the national coordination of FHP ,hoping that such strategy bring solutions for many health problems faced by the public health sector in Brazil.